Cx43 expression and function in the nervous system—implications for stem cell mediated regeneration - Meier, Carola; Rosenkranz, Katja (Frontiers in Physiology, 2014)
Pathological conditions of the brain such as ischemia cause major sensorimotor and cognitive impairments. In novel therapeutic approaches to brain injury, stem cells have been applied to ameliorate the pathological outcome. In several experimental models, including hypoxia-ischemia and trauma, transplantation of stem cells correlated with an improved functional and structural outcome. At the cellular level, brain insults also change gap junction physiology and expression, leading to altered intercellular communication. Differences in expression in response to brain injury have been detected in particular in Cx43, the major astrocytic gap junction protein, and its overexpression or deletion was associated with the pathophysiological outcome. We here focus on Cx43 changes in host tissue mediated by stem cells. Stem cell-induced changes in connexin expression, and consecutively in gap junction channel or hemichannel function, might play a part in altered cell interaction, intercellular communication, and neural cell survival, and thereby contribute to the beneficial effects of transplanted stem cells.